Biogas Production from Bakery Wastewater in Two-Stage Anaerobic Digestion System - Singharat, Kanchai; Sangkarak, Sirirat; Pongsuk, Onuma; Junyapoon*, Suwannee (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
Biogas production from bakery wastewater was studied using a semi-continuous, two-stage anaerobic digestion system, consisting of 2 l-first-stage digester and 5 l-second-stage digester under temperature of 35°C. Substrate feed rates were examined in a batch experiment by varying in the range of 50 to 200 ml/l/d. Characteristics of substrate and effluent of the digester (i.e. pH, SS, TS, VS, VFAs, COD, sCOD, TN, TPT TSO, ), biogas yields and compositions were investigated. The experimental results showed that substrate feed rate of 100 ml/l/d produced maximum yield of biogas. The biogas yield was directly proportional to concentration of VFAs in the second-stage digester. The approximate pH values in the first stage and the second stage digesters were 6.13 and 7.25, respectively. The average biogas yield of 0.481 l/ g VS removed and 0.609 l/ g sCOD removed was observed at a hydraulic retention time (HRT) of 10 days. Biogas contained 46.4%-60.8% methane. Removal efficiencies of SS, VS, COD and sCOD in this system were 85.58%, 93.35%, 87.91% and 75%, respectively. The amounts of total nitrogen and total phosphorus after digestion increased whereas that of sulfate decreased. Keywords: biogas, bakery wastewater, two-stage anaerobic digestion *Corresponding author: Tel.: 662-329-8400-11 ext. 262 Fax: 662-329-8412 E-mail: sjunyapoon68@gmail.com